The causal factors that affect the organizational performance of large-size companies in Thailand through HR analytics - Penpokai, Sukawat; Vuthisopon, Sujira; Saengnoree, Amnuay (Nurture, 2023)
Purpose: The purpose of this study is to investigate the impact of the causal factors, namely Organizational Culture (OC), Technology Adoption (TEA), and HR Competencies (HRC) on Organizational Performance (ORP), with a focus on the moderating effect of HR analytics (HRA). Design/Methodology/Approach: Data were collected using the purposive sampling method from 498 top management in the human resources department working for large-size organizations in Thailand. Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) are applied as statistical techniques to validate and test the proposed hypotheses of the conceptual framework. Findings: Results give strong supporting evidence to accept all the proposed hypotheses that the studied factors are contributing to each other and creating an impact on organizational performance. Conclusion: It is confirmed that ORC, TEA, and HRC have positively impacts on HRA and ORP. In addition, it is also confirmed that HRA acts as a moderating factor to facilitate the impact of ORC, TEA, and HRC on ORP. Research Limitations/Implications: The scope of this study only focuses on large-size organizations that operate in Thailand. Practical Implications: This study provides guidelines for an organization to improve factors that can have a positive impact on their performances. Contribution to Literature: This study serves as one of the pioneering contributions to the field of HRA and its implications for ORP.